Atypical Fibroxanthoma - Histological Diagnosis, Immunohistochemical Markers and Concepts of Therapy - Koch, Michael; Freundl, Anne J.; Agaimy, Abbas; Kiesewetter, Franklin; Kuenzel, Julian; Cicha, Iwona; Alexiou, Christoph (Anticancer Research, 2015)
Atypical fibroxanthoma (AFX) is an uncommon, rapidly growing cutaneous neoplasm of uncertain histogenesis. Thus far, there are no guidelines for diagnosis and therapy of this tumor.We included 18 patients with 21 AFX, and 2,912 patients with a total of 2,939 AFX cited in the literature between 1962 and 2014.In our cohort, excision with safety margin was performed in 100% of primary tumors. Local recurrences were observed in 25% of primary tumors and parotid metastases in 5%. Ten-year disease-specific survival was 100%. The literature research yielded 280 relevant publications. Over 90% of the reported cases were negative for cytokeratins, S100, desmin and human melanoma black 45 (HMB-45). Recurrent AFX was reported in 7.6% and metastasizing AFX in 2.75% cases. No significant differences in the recurrence and survival rates following wide local excision versus Mohs microsurgery were observed. Twenty-year disease-specific survival rate was 97.8%.A well-selected panel of immunohistochemical markers is necessary to establish AFX diagnosis with sufficient certainty. Adequately treated, AFX has an excellent prognosis, but long-term follow-up is recommended due to the potential for aggressive behavior.
EVALuna2:6738